Effect of Bayah natural zeolite for purification of waste cooking oil as feedstock of alkyd resin - Heri Heriyanto; Endang Suhendi; Nadya Fitri Asyuni; Ilham Kiki Shahila (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2022)
The waste of cooking oil was increased due to the cooking oil consumption increases. Waste cooking oil can reuse for raw material after the adsorption process with Bayah's natural zeolite, such as feedstock of alkyd resins. This paper studied the effect of the mass of Bayah natural zeolite (w/w %) on the characteristics of waste cooking oil. The Bayah natural Zeolite as adsorbent to reduce the value of free fatty acids and peroxide numbers The first stage is the preparation of waste cooking oil and Bayah natural zeolite, and then activation of Bayah natural zeolite, and the adsorption process of waste cooking oil with 15 and 30% w/w of zeolite. The results show the characteristics of waste cooking oil which before being adsorbed had an acid value of 1.51% and a peroxide value of 28.43 mek O2/kg which had passed the quality standard parameters of cooking oil quality. The effect of alkaline (NaOH 15 and 30%) activated zeolite to waste cooking oil decreases the free fatty acid content to 0.98% and 0.75%, and the peroxide value was 19.54 mek O2/kg and 18.38 mek O2/kg, respectively. The greater the amount of zeolite added the lower the acid number and peroxide value in the oil, thereby increasing the quality of the oil as raw material for alkyd resins. Minyak jelantah mengalami kenaikan seiring dengan meningkatkanya konsumsi minyak goreng. Minyak jelantah dapat digunakan kembali untuk bahan baku setelah proses adsorpsi dengan zeolit alam Bayah, seperti untuk bahan baku alkyd resin. Makalah ini mempelajari pengaruh massa zeolit alam Bayah (b/b %) terhadap karakteristik limbah minyak jelantah. Tahap pertama adalah preparasi minyak jelantah dan zeolit alam Bayah, kemudian aktivasi zeolit alam Bayah, dan proses adsorpsi minyak jelantah dengan massa zeolit 15 dan 30% b/b. Hasil penelitian menunjukkan karakteristik minyak jelantah sebelum diadsorbsi memiliki bilangan asam 1.51% dan bilangan peroksida 28.43 mek O2/kg yang telah sesuai dengan parameter baku mutu minyak goreng. Pengaruh zeolit teraktivasi alkali (NaOH 15 dan 30 %) terhadap minyak jelantah menurunkan kadar asam lemak bebas menjadi 0.98% dan 0.75%, serta bilangan peroksida masing-masing adalah 19.54 mek O2/kg dan 18.38 mek O2/kg. Semakin besar jumlah zeolit yang ditambahkan, maka semakin rendah bilangan asam dan bilangan peroksida dalam minyak, sehingga meningkatkan kualitas minyak sebagai bahan baku alkyd resin.